Acute Pharmacological Effects and Oral Fluid Concentrations of the Synthetic Cannabinoids JWH-122 and JWH-210 in Humans After Self-Administration: An Observational Study - Martínez, Lucia; La Maida, Nunzia; Papaseit, Esther; Pérez-Mañá, Clara; Poyatos, Lourdes; Pellegrini, Manuela; Pichini, Simona; Ventura, Mireia; Galindo, Liliana; Busardò, Francesco Paolo; Farré, Magí (Frontiers in Pharmacology, 2021)
Synthetic cannabinoids (SCs) are a group of new psychoactive drugs used recreationally with potential health risks. They are monitored by the EU Early Warning System since 2010 due to severe adverse effects on consumers. JWH-122 and JWH-210 are naphthoylindole SCs and potent cannabinoid receptor CB1 and CB2 agonists. Information about the effects of SCs usually is available from intoxication cases and surveys, and few studies in humans after controlled administration or observational/naturalistic studies using standardized measures of cardiovascular and subjective effects are available. The aim of this study was to evaluate the acute pharmacological effects of JWH-122 and JWH-210 recreational consumption in a 4-h observational study, and assess their disposition in oral fluid. Sixteen volunteers self-administered 1 mg dose of JWH-122 (n=8) or 2.25 mg mean dose of JWH-210 (range 2-3 mg, n=8) by inhalation (smoking). Physiological parameters including blood pressure (systolic and diastolic), heart rate and cutaneous temperature were measured. A set of Visual Analog Scales (VAS), the 49-item short form version of the Addiction Research Centre Inventory (ARCI) and the Evaluation of the Subjective Effects of Substances with Abuse Potential (VESSPA-SSE) were used for the evaluation of subjective effects. Oral fluid was collected at baseline, 10, 20 and 40 min, and 1, 2, 3 and 4 h after self-administration. Statistically significant increases in systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were observed after JWH-122 self-administration but not after JWH-210 self-administration. JWH-210 self-administration produced significant changes in subjective drug effects, similar to those induced by THC (intensity, high, positive effects and hunger). The subjective effects following JWH-122 consumption were minimal. The maximal effects were mostly observed 20 min after intake. JWH-122 and JWH 210 oral fluid concentration reached a peak 20 min after administration and were not detected after 3 h. The results demonstrated a different pattern of effects of these two SCs. Due to the limitations of our observational study, further research with a larger sample and controlled studies is needed to better define the acute pharmacological effect and health risk profile of JWH-122 and JWH-210.